2022
DOI: 10.1038/s41598-022-25801-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effective screening strategies for safe opening of universities under Omicron and Delta variants of COVID-19

Abstract: As new COVID-19 variants emerge, and disease and population characteristics change, screening strategies may also need to change. We develop a decision-making model that can assist a college to determine an optimal screening strategy based on their characteristics and resources, considering COVID-19 infections/hospitalizations/deaths; peak daily hospitalizations; and the tests required. We also use this tool to generate screening guidelines for the safe opening of college campuses. Our compartmental model simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The study setting was the US in 80 studies, and the US combined with other countries in 12 studies. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The target population was the general population in 68 studies and specific sub-populations in 24 studies, including university population (n = 11), 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 school population (n = 5), 39 , 40 , 41 , 42 , 43 congregation setting population (n = 5), 44 , 45 , 46 , 47 , 48 children (n = 2), 18 , 49 and wildland firefighting workforce (n = 1). 50 Vaccine intervention strategies were studied interventions in 69 studies, and vaccines combined with other strategies (including non-pharmaceutical interventions (NPIs) and screening) in 23 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study setting was the US in 80 studies, and the US combined with other countries in 12 studies. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The target population was the general population in 68 studies and specific sub-populations in 24 studies, including university population (n = 11), 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 school population (n = 5), 39 , 40 , 41 , 42 , 43 congregation setting population (n = 5), 44 , 45 , 46 , 47 , 48 children (n = 2), 18 , 49 and wildland firefighting workforce (n = 1). 50 Vaccine intervention strategies were studied interventions in 69 studies, and vaccines combined with other strategies (including non-pharmaceutical interventions (NPIs) and screening) in 23 studies.…”
Section: Resultsmentioning
confidence: 99%
“… 50 Vaccine intervention strategies were studied interventions in 69 studies, and vaccines combined with other strategies (including non-pharmaceutical interventions (NPIs) and screening) in 23 studies. 23 , 27 , 29 , 30 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 41 , 44 , 45 , 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Seventy-three studies used compartmental models, and agent-based models were employed in 19 studies. 23 , 24 , 30 , 32 , 33 , 37 , 39 , 40 , 41 , 43 , 45 , 46 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Table 1 shows the summary of study characteristics included in this review, and a full description of included studies can be found in Supplementary Table S1 in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
“…Both in-person and virtual screening technology implementations require the compliance of participants in the screening procedure. Screening compliance reportedly leads to fewer infections in the modeling of screening strategies (Rabil et al, 2022), and therefore the level of participation required is an important consideration in screening procedures. In a study by Kennedy et al (2021) front-door screeners reported that although they felt the majority of those being screened were often or always willing to participate found that some ignored, refused, or avoided screening stations.…”
Section: Screening Technology Limitationsmentioning
confidence: 99%